Aggregating digital resources in an e-learning platform: A case study of a Malaysian public university’s compliance with copyright - Tay, Pek San; Tay, Pek San (Malaysian Journal of Library and Information Science, 2017)
San, T. P. (2015). Aggregating digital resources in an e-learning platform: A case study of a Malaysian public university’s compliance with copyright. Malaysian Journal of Library & Information Science, Vol.20, no. 1: 1-18 This study investigates the copyright issues that arise when course instructors aggregate digital resources in an e-learning platform, and how copyright concerns among instructors influence the approaches used by them in aggregating such resources. The objective of the study is to explore how the aggregation of digital resources in an e-learning platform may be optimized without infringing copyright in the digital content. The study was set up in a Malaysian public research university which had introduced an e-learning platform to its academic staff since 2003. It involved the following data collection techniques: survey questionnaires that were distributed to course instructors in various faculties of the university; semi-structured informal interviews with instructors; and observation of instructors’ participation in training workshops on the use of the e-learning platform. Findings indicate that most course instructors have a general awareness of the copyright issues that are involved and, to some extent, this has influenced the approaches which they adopted when aggregating digital resources for their students. It was found that the use of linking and embedding were ways of aggregating digital resources in e-learning platforms which are consistent with copyright law. In addition, this paper suggests that institutions of higher learning should set up a website to provide guidance on possible approaches that could be adopted to aggregate digital resources in e-learning platforms in accordance with copyright law. The website should include information on how the fair dealing provision in the Copyright Act 1987 may be utilized in the teaching process.